Effectiveness of ionic stabilization in the mitigation of soil volume change behavior. (July 2021) - Al-Dakheeli, Hussein; Arefin, Sharif; Bulut, Rifat; Little, Dallas
Abstract: Ionic stabilization is one of the non-traditional methods of soil stabilization. It is an advantageous stabilization method of being economic and utilizing liquid agents that can easily diffuse through soil and stabilize it. While several studies have been undertaken on ionic stabilization, the experience is still not sufficient enough and thus more research work is needed to understand the mechanism of ionic stabilization. This paper presents experimental results of soils treated in the field and the laboratory by an ionic acidic stabilizer. The experimental tests involve one-dimensional swelling, three-dimensional shrinkage, and suction measurements on treated and native natural soils from Texas and Oklahoma. The results show that the stabilizer minimized the percent swell at least to the half but had no considerable effect on the shrinkage. The results of wetting–drying cycles showed a significant reduction of the volume change rate of treated soils. Treated soil in the field revealed a noticeable reduction in suction. However, suction at high values obtained by a chilled-mirror psychrometer of treated soils manifested no considerable change from natural soils. Overall, the variation in suction measurements came consistent with the volume change results. The latter finding provides an encouragement in utilizing suction as a tool to examine the effectiveness of ionic stabilization.